Early Detection of Mental Health Problems Health Personnel During Covid-19 Pandemic - Dwi Heppy Rochmawati; Betie Febriana; Sri Mulyono (Indonesian Journal of Global Health Research, 2022)
The determination of the pandemic condition by WHO has caused various public responses and psychosocial problems. This research is important because the spread of the virus is very fast, widespread and mass causes cases to increase and have an impact not only on physical but also psychological conditions, causing mental health problems. Various efforts have been made by the government to combat the epidemic, community participation involving individuals, families and community groups is urgently needed to solve this problem. The purpose of this study was to identify mental health problems experienced by health workers due to the COVID-19 pandemic and to develop a model for early detection of mental health problems. This research method uses a quantitative approach with three stages of research. The first research stage is the exploration of mental health problems experienced by health workers. The second stage is developing a model for early detection of mental health problems and providing mental health and psychosocial support. The third stage is the use of early detection models in handling mental health problems for health workers. The method of data collection was carried out using a Self-Reporting Questionnaire (SRQ) questionnaire and the implementation of Habit Adaptation met the criteria. The sample was taken using purposive sampling technique. Data was obtained using a questionnaire and analized by the paired t test. The results showed that there was a difference between pre-test and post-test, meaning that that interventions are effective in addressing physical and psychosocial health problems.